Elämän pokeri - Ruusumaa, Jukka; Anttila, Vesa; Elo, Heikki; Kosunen, Rele; Kuorikoski, Pekka; Lehtonen, Harri, (rumpali); Lönnholm, Kim; Mattila, Saku; Murtojärvi, Henri; Murtojärvi, Johan; Mynttinen, Timo; Naatula, Ilkka; et al. (Sata-Artistit, 2000)
11 kappaletta.
Keywords: Ruusumaa, Jukka, : 1962- : albumit